After Hitler recivilizing Germans, 1945-1995 - Jarausch, Konrad Hugo (Oxford University Press, 2006)
How did the Germans manage to recover from the shattering experience of defeat in World War II and rehabilitate themselves from the unspeakable crimes of the Holocaust? This book seeks to answer this important question.